Audit of practice in sudden unexpected death in epilepsy (SUDEP) post mortems and neuropathological findings. (25th September 2015) - Thom, Maria; Michalak, Zuzanna; Wright, Gabriella; Dawson, Timothy; Hilton, David; Joshi, Abhijit; Diehl, Beate; Koepp, Matthias; Lhatoo, Samden; Sander, Josemir W.; Sisodiya, Sanjay M.
Abstract : Aims: Sudden unexpected death in epilepsy (SUDEP) is one of the leading causes of death in people with epilepsy. For classification of definite SUDEP, a post mortem (PM), including anatomical and toxicological examination, is mandatory to exclude other causes of death. We audited PM practice as well as the value of brain examination in SUDEP. Methods: We reviewed 145 PM reports in SUDEP cases from four UK neuropathology centres. Data were extracted for clinical epilepsy details, circumstances of death and neuropathological findings. Results: Macroscopic brain abnormalities were identified in 52% of cases. Mild brain swelling was present in 28%, and microscopic pathologies relevant to cause or effect of seizures were seen in 89%. Examination based on whole fixed brains (76.6% of all PMs), and systematic regional sampling was associated with higher detection rates of underlying pathology ( P < 0.01). Information was more frequently recorded regarding circumstances of death and body position/location than clinical epilepsy history and investigations. Conclusion: Our findings support the contribution of examination of the whole fixed brain in SUDEP, with high rates of detection of relevant pathology. Availability of full clinical epilepsy‐related information at the time of PM could potentially further improve detection through targeted tissue sampling. Apart from confirmation of SUDEP, complete neuropathological examination contributes to evaluation of risk factors as well as helping to direct future research into underlying causes. Abstract : The importance of examination of the whole fixed brain complemented by systematic regional sampling for histology to demonstrate relevant neuropathological abnormalities in sudden unexpected death in epilepsy (SUDEP) is highlighted by this study.